2015
DOI: 10.14367/kjhep.2015.32.5.63
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of occupational stress and psychosocial stress to health promotion behavior in female office workers and emotional labor workers for sales

Abstract: Objectives: The aim of this study was to evaluate the relationship of occupational stress and psychosocial stress to health promotion behaviors depending on characteristics of female office workers and emotional labor workers for sales. Methods: A survey of 207 female service workers engaging in sales of cosmetics in major department stores and 149 females working in the offices of cosmetics companies was carried out using a self-administered questionnaire. Results: It showed a significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As a result, many smokers may view these healthy behaviors as ineffective in dealing with their immediate stresses. Evidence has shown that stress has a negative relationship with behaviors that promote health (Han et al, 2015), so smokers are even less likely to engage in such behaviors (Thanavaro, 2005; Thanavaro, Moore, Anthony, Narsavage, & Delicath, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many smokers may view these healthy behaviors as ineffective in dealing with their immediate stresses. Evidence has shown that stress has a negative relationship with behaviors that promote health (Han et al, 2015), so smokers are even less likely to engage in such behaviors (Thanavaro, 2005; Thanavaro, Moore, Anthony, Narsavage, & Delicath, 2006).…”
Section: Introductionmentioning
confidence: 99%